Chemical Control of Coffee Leaf Diseases in an Integrated Pest Management System: A Literature Review - Isnaini, Maidatul; Violita, Violita (Jurnal Biologi Tropis, 2026)
Coffee leaf diseases, particularly coffee leaf rust caused by Hemileia vastatrix, remain one of the major constraints to coffee production in Indonesia and other coffee-producing countries, causing yield losses of up to 50% under severe infection. Synthetic fungicides are still the primary control strategy because of their rapid and reliable disease suppression. This review aimed to evaluate the effectiveness of synthetic fungicides in managing coffee leaf diseases, compare the performance of different fungicide groups, and identify recent trends in their application. A literature review was conducted using peer-reviewed articles published between 2015 and 2025 retrieved from Scopus, Web of Science, ScienceDirect, and Google Scholar. The search employed the keywords “coffee leaf rust,” “Hemileia vastatrix,” “synthetic fungicide,” “triazole,” “strobilurin,” and “coffee disease management.” Only English- and Indonesian-language articles reporting fungicide efficacy under field or greenhouse conditions were included. The reviewed studies consistently showed that triazole- and strobilurin-based fungicides were the most effective, generally reducing coffee leaf rust severity by 60–90% when applied at the early stages of infection. However, repeated application of single-mode-of-action fungicides increases the risk of pathogen resistance and environmental contamination. This review highlights the comparative effectiveness of major synthetic fungicide groups and emphasizes that their use should be integrated with resistant cultivars, cultural practices, and fungicide rotation within an Integrated Pest Management (IPM) framework to support sustainable coffee production. Further studies are recommended to optimize fungicide rotation strategies and evaluate environmentally safer alternatives.